Суспільні трансформації як складова державно- управлінських реформ : інституціональний вимір - Липовська, Наталія (My University, 2017)
The article analyzes the problems of institutional transformation management from the positions of neoinstionalism, reveals the advantages and disadvantages imports institutions emphasize controlover social transformation, which invariably accompany public-management reform.
Social transformations as a component of public management reforms: institutional measurement
Keywords: державне управління; місцеве самоврядування; політична відповідальність; governance; institution; institutional transformation